SAT0366 Vitamin D levels and bone mineral density in systemic sclerosis. (23rd January 2014) - Atteritano, M.; Bagnato, G.; Miceli, G.; Sangari, D.; Talotta, R.; Tamburello, A.; Morgante, S.; Bagnato, G.
Abstract : Background: Systemic sclerosis (SSc) is a chronic disease characterized by increased synthesis and deposition of collagen in skin and connective tissue, vascular alteration and immunological disturbances. Recently was demonstrated that SSc itself is a risk factor for osteoporosis. Several other studies had observed a relationship between low bone density and systemic sclerosis Objectives: The aim of our study was to investigate whether SSc is arisk factor for osteoporosis, and what are the most probable causative factors that negatively regulate bone metabolism in these patients. Methods: We recruited from September 2007 to March 2010 fifty-four consecutive postmenopausal women with newly systemic sclerosis (SSc) at the Unit of Rheumatology of the University of Messina, and 54 healthy postmenopausal women matched for age, body mass index (BMI), menopausal age and smoking habits served as the control group. All the patients with scleroderma met the diagnostic criteria for SSc. None of the subjects in both group were on supplementation with calcium and vitamin D. Bone mineral density was measured in all women in both groups by dual energy-x-ray absorptiometry at spine and femur, and by ultrasonography at calcaneus. Serum levels of 25-hydroxivitamin D, parathyroid hormone and bone turnover markers were examined. All patient had a spine X-ray to ascertain the presence of vertebral fractures. Results: bone mineral density at lumbar spine, femoral neck and total femur and ultrasound parameter at calcaneus were significantly lower in scleroderma compared with controls; bone turnover markers and parathyroid hormone level were significantly higher in scleroderma compared with controls, while serum of 25-hydroxivitamin D was significantly lower. In scleroderma group the serum levels of 25-hydroxivitamin significantly correlated with parathyroid hormone levels, bone mineral density, stiffness index and bone turnover markers. One or more moderate or severe vertebral fractures were found in 13 patients with scleroderma, wherease in control group only one patient had a mild vertebral fracture Conclusions: Vertebral fractures are frequent in patient with scleroderma. Our data shows that scleroderma is a risk factors for osteoporosis and suggest that lower levels of 25-hydroxivitamin D may play a role in the pathogenetic process underlying osteopenia in these patients. References: Souza RB, Borges CT, Takayama L, Aldrighi JM, Pereira RM (2006). Systemic sclerosis and bone loss: the role of the disease and body composition. Scand J Rheumatol 35:384-387. Carbone L, Tylavsky F, Wan J, McKown K, Cheng S (1999) Bone mineral density in scleroderma. Rheumatology (Oxford) 37:1–2 Di Munno O, Mazantini M, Massel P, Ferdeghini M, Petaro N, Latorraca A, Ferri C (1995) Reduced bone mass and normal calcium metabolism in systemic sclerosis with and without calcinosis. Clin Rheumatol 14:407–412 La Montagna G, Vatti M, Valenti G, Tirri G (1991) Osteopenia in systemic sclerosis evidence of a participating role of earlier menopause. Clin Rheumatol 10:18–22 Genant HK, Wu CY, van Jujik C, Nvitt MC (1993). Vertebral fracture assessment using a semiquantitative technique. J Bone Miner Res 8:1137-48 Disclosure of Interest: None Declared